Pedagogia social e valores : o resgate do direito à educação - Wegner, Maraike (2008)
Social Pedagogy is a science that studies the ways of including both those who deviate and those who are deviated from social participation legitimate environments. In order that social inclusion takes place, these children and youths should play an active role in specific learning and socializing processes that enable improvements in their apprenticeship and socialization. Pedagogical intervention is a mediation in learning activity and a way of conducting and purposing educational processes through relationships. Those children and youths require a mediation of new values in order that they can collectively take part in teaching environments made legitimate by society. Those interventions intercede in single learning and socializing processes by means of the mediation of practical, attitudinal content. Apprenticeship takes place through one s interaction with others and the environment, with the society where one lives. Group problem solving stimulates internal evolutionary traits that act when a child interacts with others. The interaction among others is based on values that guide our behavior. Those values describe the valuations that qualify acts, people, feelings, behaviors and/or the moral valuations of our behavior. Faith is composed of the values that have centralizing power in our lives; it is relational and seeks equity among the people. In order that equity is met, common values shall be the location where social educators will lay their hearts . Common values stand for the welfare of the insertion group and direct one s attention towards favorable conditions so that everyone can evolve. While every person is assured basic rights to social inclusion, many are not able to benefit from that. Social Pedagogy is an alternative for achieving social inclusion and the required educational justice.